Biofilm production is not associated with poor clinical outcome in 485 patients with Staphylococcus aureus bacteraemia. (June 2018) - Guembe, M.; Alonso, B.; Lucio, J.; Pérez-Granda, M.J.; Cruces, R.; Sánchez-Carrillo, C.; Fernández-Cruz, A.; Bouza, E.
Abstract: Objectives: Staphylococcus aureus biofilm may constitute a major cause of virulence. Our main objective was to analyse whether there was an association between biofilm production and poor outcome in patients with S. aureus bacteraemia. Methods: We studied 485 S. aureus strains isolated from the blood of patients with bacteraemia from 2012 to 2015. We assessed in vitro biomass production using crystal violet assay and metabolic activity using tetrazolium salt assay. Strains were classified in tertile ranks as follows: low biomass producers, moderate biomass producers, high biomass producers, low metabolic activity, moderate metabolic activity and high metabolic activity. We excluded from analysis strains with moderate crystal violet and tetrazolium salt values. We defined poor outcome as fulfillment of one or more of the following conditions: 30-day attributable mortality, infective endocarditis, persistent bacteraemia and recurrent bacteraemia. Results: Outcome was poor in 199 (41.0%) of 485 S. aureus bacteraemia episodes. The distribution of poor outcome with respect to biomass production and metabolic activity was as follows: low biomass producers, 36.6% vs. high biomass producers, 43.2% (p 0.26); and low metabolic activity, 43.5% vs. high metabolic activity, 36.2% (p 0.91). The presence of methicillin-resistant S. aureus was the only characteristic that was more likely to be present in the high metabolic activity group (17.4% vs. 39.3%, p < 0.001). Conclusions: Biofilm production, as determined by any of the methods used in the present study, is not associated with poor outcome in patients with S. aureus bacteraemia. Graphical abstract: